4.9k views
3 votes
Rewrite the following expression.

Rewrite the following expression.-example-1

2 Answers

2 votes

We have been given the expression


x^{(9)/(7)}

We have the exponent rule


x^{(a)/(b)}= x^{a^{((1)/(b))}}

Using this rule, we have


x^{(9)/(7)}= x^{9^{((1)/(7))}}

Now, using the fact that
x^{(1)/(n)}=\sqrt[n]{x}, we get


x^{(9)/(7)}= \sqrt[7]{x^9}\\ \\ x^{(9)/(7)}=\sqrt[7]{x^7* x^2}\\ \\ x^{(9)/(7)}=x\sqrt[7]{x^2}

D is the correct option.

User JasonWoof
by
5.1k points
2 votes

Answer

D. x (⁷√x²)


Step-by-step explanation

x⁹/⁷ = ⁷√(x⁹)

= ⁷√(x⁷ × x²)

= (⁷√x⁷) × (⁷√x²)

= x (⁷√x²)

The answer is D.

User Gili
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.